Pengaruh Strategi Pemasaran Digital, Harga dan Kualitas Produk terhadap Kepuasan Pelanggan Mie Gacoan - Deni Setiawan; Zulfa Irawati (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the effect of digital marketing strategy, the price offered, product quality on customer satisfaction Mie Gacoan in Surakarta. In recent years, many students have been interested in buying Gacoan Noodles. This resulted in an increase in the sales volume of Gacoan Noodles in Surakarta, as well as the addition of new branches in various Surakarta areas. This research is a quantitative research, involving 200 student respondents in Surakarta. The data in this study were collected using a questionnaire via a Google form using a Likert measurement scale. The data analysis technique of this study used multiple linear regression with the SPSS version 21 program. The results showed that the Digital Marketing Strategy had a significant effect on customer satisfaction on Mie Gacoan in Surakarta, Price had a significant effect on customer satisfaction on Mie Gacoan in Surakarta, Product quality had a significant effect on customer satisfaction Gacoan noodles in Surakarta. The coefficient of determination with Adjusted R2 is 56.1%, this means that the independent variables in the model (digital marketing strategy, price, and product quality) explain the variation in customer satisfaction of Mie Gacoan in Surakarta by 55.1%.